Carcinoma of the ovary after vaginal hysterectomy - Lichtinger, Moisés (2015)
During the years 1969 - 1982, 369 patients with ovarian carcinoma were surgically explored Hospital Medical Center of the University of Miami. Eight patients (2.1%) had previous vaginal hysterectomy for benign disease. All patients had undergone hysterectomy 40 years at the time of vaginal surgery. Survival and results of second laparotomy for ovarian carcinoma in these 8 patients were affected by the presence of ascites, surgical stage and the presence of residual tumor after cytoreductive surgery. Based on our experience, our technique is presented for vaginal prophylactic salpingo-oophorectomy.